Does proximal rectus femoris release influence kinematics in patients with cerebral palsy and stiff knee gait? - Vegvari, Dóra; Wolf, Sebastian Immanuel; Heitzmann, Daniel; Klotz, Matthias C. M.; Dreher, Thomas (Clinical orthopaedics and related research, 2013)
Background: Stiff gait resulting from rectus femoris dysfunction in cerebral palsy commonly is treated by distal rectus femoris transfer (DRFT), but varying outcomes have been reported. Proximal rectus femoris release was found to be less effective compared with DRFT. No study to our knowledge has investigated the effects of the combination of both procedures on gait. - Questions/purposes: We sought to determine whether an additional proximal rectus release affects knee and pelvic kinematics when done in combination with DRFT; specifically, we sought to compare outcomes using the (1) range of knee flexion in swing phase, (2) knee flexion velocity and (3) peak knee flexion in swing phase, and (4) spatiotemporal parameters between patients treated with DRFT, with or without proximal rectus release. Furthermore the effects on (5) anterior pelvic tilt in both groups were compared. - Methods: Twenty patients with spastic bilateral cerebral palsy treated with DRFT and proximal rectus femoris release were matched with 20 patients in whom only DRFT was performed. Standardized three-dimensional gait analysis was done before surgery, at 1 year after surgery, and at a mean of 9 years after surgery. Basic statistics were done to compare the outcome of both groups. - Results: The peak knee flexion in swing was slightly increased in both groups 1 year after surgery, but was not different between groups. Although there was a slight but not significant decrease found the group with DRFT only, there was no significant difference at long-term followup between the groups. Timing of peak knee flexion, range of knee flexion, and knee flexion velocity improved significantly in both groups, and in both groups a slight deterioration was seen with time; there were no differences in these parameters between the groups at any point, however. There were no group differences in spatiotemporal parameters at any time. There were no significant differences in the long-term development of anterior pelvic tilt between the groups. - Conclusions: The results of our study indicate that the short- and long-term influences of adding proximal rectus femoris release on the kinematic effects of DRFT and on pelvic tilt in children with cerebral palsy are negligible. - Level of Evidence: Level III, therapeutic study. See the Guidelines for Authors for a complete description of levels of evidence.